Characteristic of clinical trials related to traumatic brain injury registered on ClinicalTrials.gov over the past two decades (2004–2023) - Guo, Ruili; Yang, Qingya; Zhou, Xuan; Li, Shining; Liu, Yao (Frontiers in Medicine, 2024)
The aim of this report is to provide a comprehensive overview of clinical trials and protocols related to traumatic brain injury over the past two decades.We collected information on clinical trials related to traumatic brain injury (TBI) from the ClinicalTrials.gov database, identified key categorical variables, and assessed their characteristics.A total of 367 TBI-related trials were identified for analysis. All identified trials were interventional clinical trials. Most trials were small-scale, with 75.2% enrolling 1-100 participants, and only about 20% were funded by industry or the National Institutes of Health (NIH). In most trials, participants were gender-neutral (96.5%), and the primary age group was adults and older adults (56.9%). Of all identified TBI trials, 78.2% were randomized, and 69.4% were blinded. Additionally, the primary purpose of 297 trials (80.9%) was treatment, with drug therapy as the most common intervention. A total of 153 trials (41.7%) were completed; however, only 58 trials submitted results to the registry. Furthermore, 81 trials (22.1%) were discontinued early, primarily due to recruitment problems. Clinical trials started between 2004 and 2013 reported a higher proportion of results compared with those started between 2014 and 2023 (35.1% vs. 11.1%, P<0.001). In addition, between 2014 and 2023, there was an increase in trials for diagnostic purposes (2.4% vs. 6.5%, P<0.001).Based on the data collected from the ClinicalTrials.gov, our study reveals that most clinical trials related to TBI focus on drug-related treatments, underreporting remains a significant concern, and greater emphasis should be placed on improving the publication and dissemination of clinical trial results.